Constructions in French - Bouveret, Myriam; Legallois, Dominique (Constructional approaches to language., 2012)
My concern is the relationships between grammar and expressivity which have always remained represented a minority, if not a marginal, interest in linguistics. The paper deals with the construction 'P, histoire de inf.' (Prends quelques jours de repos, histoire de te changer les idées 'take a few days' rest, just to have a break from everything'). It is shown, from a diachronic perspective, that the construction expresses an attitudinal meaning, the speaker's stance. The paper argues that, although expressivity and attitude meaning have usually been relegated to a secondary role.